Changing prostaglandin E2 (PGE2) signaling during lesional progression and exacerbation of endometriosis by inhibition of PGE2 receptor EP2 and EP4. (2nd December 2021) - Huang, Qingqing; Liu, Xishi; Guo, Sun‐Wei
Abstract: Purpose: We investigated the change, if any, in prostaglandin E2 (PGE2 ) signaling in endometriotic lesions of different developmental stages in mouse. In addition, we evaluated the effect of treatment of mice with induced deep endometriosis (DE) with inhibitors of PGE2 receptor subtypes EP2 and EP4 and metformin. Methods: Three mouse experimentations were conducted. In Experiment 1, female Balb/C mice were induced with endometriosis or DE and were serially sacrificed after induction. Experiments 2 and 3 evaluated the effect of treatment with EP2 and EP4 inhibitors and metformin, respectively, in mice with induced DE. Immunohistochemistry analysis of COX‐2, EP2, and EP4, along with the extent of lesional fibrosis, was evaluated. Results: The immunostaining of COX‐2, EP2, and EP4 turned from activation to a stall as lesions progressed. Treatment with EP2/EP4 inhibitors in DE mice exacerbated endometriosis‐associated hyperalgesia and promoted fibrogenesis in lesions even though it suppressed the PGE2 signaling dose‐dependently. In contrast, treatment with metformin resulted in increased PGE2 signaling, concomitant with improved hyperalgesia, and retarded lesional fibrogenesis. Conclusions: The PGE2 signaling diminishes as endometriotic lesions progress. Treatment with EP2/EP4 inhibitors in DE mice exacerbates endometriosis, but metformin appears to be promising seemingly through the induction of the PGE2 signaling.